Pengaruh Komunikasi Dan Kerjasama Tim Melalui Motivasi Kerja Terhadap Kinerja Pegawai Sebagai Variabel Intervening Pada Dinas Peternakan Dan Kesehatan Hewan Provinsi Sumatera Barat - Elsi Darmayanti; Ramdani Bayu Putra; Nila Pratiwi (GLOBAL SCIENTS PUBLISHER, 2025)
The aim of this research is to find out how much influence communication and teamwork through work motivation have on employee performance with intervening variables at the West Sumatra Province Animal Husbandry and Animal Health Service Office. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample for this study were employees of the West Sumatra Province Animal Husbandry and Animal Health Service. There is a positive and significant influence between Communication on Work Motivation at the Animal Husbandry and Animal Health Service of West Sumatra Province. There is a positive and significant influence between Teamwork on Work Motivation at the West Sumatra Province Animal Husbandry and Animal Health Service. There is a positive and significant influence between Communication on Employee Performance at the West Sumatra Province Animal Husbandry and Animal Health Service. There is a positive and insignificant influence between Teamwork on Employee Performance at the Animal Husbandry and Animal Health Service of West Sumatra Province. There is a positive and insignificant influence between Work Motivation on Employee Performance at the West Sumatra Province Animal Husbandry and Animal Health Service.